2009
DOI: 10.1029/2009gl040006
|View full text |Cite
|
Sign up to set email alerts
|

Bottom pressure signals at the TAG deep‐sea hydrothermal field: Evidence for short‐period, flow‐induced ground deformation

Abstract: [1] Bottom pressure measurements acquired from the TAG hydrothermal field on the Mid-Atlantic Ridge (26°N) contain clusters of narrowband spectral peaks centered at periods from 22 to 53.2 minutes. The strongest signal at 53.2 min corresponds to 13 mm of water depth variation. Smaller, but statistically significant, signals were also observed at periods of 22, 26.5, 33.4, and 37.7 min (1 -4 mm amplitude). These kinds of signals have not previously been observed in the ocean, and they appear to represent vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
1
1
Order By: Relevance
“…This may, however, be an oversimplified view. Pressure probe data for the TAG hydrothermal field shows periodic ground deformation that have been interpreted with a geyser-like mechanism [Sohn et al, 2009], yet TAG presents no craters. Tilt cycles with similar periods as those described at TAG by Sohn et al [2009] have been measured at the Logatchev field [Fabian and Villinger, 2008].…”
Section: Smoking Craters: Results Of Explosivementioning
confidence: 99%
See 1 more Smart Citation
“…This may, however, be an oversimplified view. Pressure probe data for the TAG hydrothermal field shows periodic ground deformation that have been interpreted with a geyser-like mechanism [Sohn et al, 2009], yet TAG presents no craters. Tilt cycles with similar periods as those described at TAG by Sohn et al [2009] have been measured at the Logatchev field [Fabian and Villinger, 2008].…”
Section: Smoking Craters: Results Of Explosivementioning
confidence: 99%
“…Pressure probe data for the TAG hydrothermal field shows periodic ground deformation that have been interpreted with a geyser-like mechanism [Sohn et al, 2009], yet TAG presents no craters. Tilt cycles with similar periods as those described at TAG by Sohn et al [2009] have been measured at the Logatchev field [Fabian and Villinger, 2008]. These authors suggested that pressure fluctuations occur in the hydrothermal upflow zone with a periodicity comparable to those measured near on-land geysers [Nishimura et al, 2006].…”
Section: Smoking Craters: Results Of Explosivementioning
confidence: 99%
“…The region 5 in Fig. 5(e) is associated with a region that includes the TAG vent field (deMartin et al 2007; Sohn et al 2009). Again, the high levels of seismicity are linked to a region where detachment faults are known to exist.…”
Section: Resultsmentioning
confidence: 99%
“…The term geyser is now also used to describe episodic discharge of multiphase fluids in engineering (e.g., Casarosa et al 1983, Hung & Shyu 1992, Kagami 2010 and geothermal wells that erupt episodically. Geyser-like behavior in natural systems has been observed on the ocean floor (Tryon et al 1999, Furushima et al 2009, Sohn et al 2009) and is inferred to occur on Saturn's moon Enceladus (Porco et al 2006, Brilliantov et al 2008) and Neptune's moon Triton ). Here we focus on hot springs that intermittently discharge liquid water, steam, and noncondensable gas at temperatures that are close to the boiling temperature of pure water for their respective elevations (Figure 1).…”
Section: Introductionmentioning
confidence: 93%